Mass transfer models for the adsorption of Acid Red 357 and Acid Black 210 by tannery solid wastes - Jeferson S Piccin; Mariliz Guterres; Nina Paula G Salau; Guilherme L Dotto (Adsorption Science & Technology)
Diffusional mass transfer models with and without external resistance were applied to represent the adsorption of Acid Red 357 (AR357) and Acid Black 210 (AB210) by tannery solid wastes. The mass transfer parameters, such as, external mass transfer coefficient ( k f ), surface diffusion coefficient ( D s ), and Biot number ( B i ) were estimated and interpreted. It was found that the two models agreed with the experimental data and, very similar values of the parameters were obtained. This indicated that the external mass transfer mechanism can be neglected. Then, the model without external resistance, which is simpler, can be used. The D s values ranged from 5.01 × 10 −13 to 1.30 × 10 −12  m 2  s −1 for AR357 and from 3.19 × 10 −14 to 5.38 × 10 −14  m 2  s −1 for AB210. The high values of the B i number confirmed that the adsorption of AR357 and AB210 on tannery solid wastes was controlled by surface diffusion.